2002
DOI: 10.1002/bdd.286
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective halofantrine and desbutylhalofantrine disposition in the rat: cardiac and plasma concentrations and plasma protein binding

Abstract: Halofantrine (HF) is a chiral antimalarial drug known to cause cardiac arrhythmias in susceptible patients. In this study, the cardiac uptake and plasma protein binding of HF and desbutylhalofantrine (DHF) enantiomers were examined in the rat. Rats were given 2 mg/kg of either HF HCl or DHF HCl intravenously, then sacrificed at various times after dosing. Specimens were assayed using stereospecific methods. Uptake of HF and DHF enantiomers into heart was rapid. Substantial concentrations of both HF and DHF ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
4
10
0
Order By: Relevance
“…These findings likely reflect a gradual change to the proportion of the (+) enantiomer present in systemic blood. Previous data have shown that systemic levels of the (+)-Hf enantiomer in both human and rat are approximately 1.5 times higher than its antipode [1][2][3][4][5][6][7], and preliminary plasma assays performed in our laboratory have indicated that the same trend is followed in the dog (data not shown). At later time periods, when intestinal lymphatic transport has slowed, an increasing proportion of the Hf in thoracic lymph is present as a result of equilibration of Hf across lymphatic and blood capillaries.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…These findings likely reflect a gradual change to the proportion of the (+) enantiomer present in systemic blood. Previous data have shown that systemic levels of the (+)-Hf enantiomer in both human and rat are approximately 1.5 times higher than its antipode [1][2][3][4][5][6][7], and preliminary plasma assays performed in our laboratory have indicated that the same trend is followed in the dog (data not shown). At later time periods, when intestinal lymphatic transport has slowed, an increasing proportion of the Hf in thoracic lymph is present as a result of equilibration of Hf across lymphatic and blood capillaries.…”
Section: Resultssupporting
confidence: 64%
“…relative enrichment of the (+)-enantiomer (data not shown) [1][2][3][4][5][6][7]. transport of the drug-lipoprotein complex via the intestinal lymphatic to the thoracic lymph.…”
Section: Resultsmentioning
confidence: 93%
“…9 As such, stereoselectivity in the CL of HF enantiomers is highly dependent on CLint and the degree of plasma protein binding, which is reportedly high. 14,15 Because in rat the plasma unbound fraction is the same for both HF enantiomers, 14 stereoselectivity in CLint of plasma unbound drug is expected to be a major contributor to stereoselectivity in CL of HF. Indeed, all metabolic assessments involving harvested hepatic microsomes, and the predominant metabolizing recombinant CYP3A2, in which (À)-DHF was preferentially formed, were in line with this belief.…”
Section: Discussionmentioning
confidence: 99%
“…This study was the to provide information regarding LDL chiral selectivity. In another study, halofantrine enantiomers showed some stereoselectivity for lipoprotein binding in vitro , but they did not show stereoselectivity for plasma protein binding 115 .…”
Section: Stereoselectivity Of Plasma Protein Binding To Chiral Drugsmentioning
confidence: 93%